Experimental modelling of Alzheimer's disease for therapeutic screening - Laura Blaikie; Graeme Kay; Patricia Maciel; Paul Kong Thoo Lin (Elsevier, 2022)
Neurodegenerative diseases, including Alzheimer's disease (AD), pose a significant and urgent challenge to healthcare systems worldwide. With an increasing life expectancy, these progressive age-related disorders are expected to rise exponentially. No cure currently exists for AD, and the aetiology remains poorly understood. Furthermore, AD drug development faces one of the highest failure rates. Thus, a review of the experimental modelling of the disease is crucial to understanding how the current disease models can be applied to gain useful results while also considering their limitations. Disease models include in vitro, in vivo, ex vivo, and in silico systems as well as clinical trials. These systems are important for testing potential therapeutics to advance drug development, in addition to modelling the pathology of the disease to gain a greater understanding of the cause and progression. This review will discuss the current experimental models employed for the study of AD with the aim of providing an overview of how they are used and discuss their benefits and drawbacks as model systems, as well as highlighting the potential future of the experimental modelling of AD.